Debates of Corruption and Integrity
VIII, 242 p.
Keywords: Two aspects link together the notions of corruption and integrity from an epistemological perspective: the complexity of defining the two notions, and their richness in forms. This volume brings together the perspectives of six disciplines - business, political science, law, philosophy, anthropology and behavioural science - to the debate on integrity and corruption. The main goal is to promote a fruitful interdisciplinary dialogue on complex themes such as integrity and corruption in business and politics. The book investigates possible ways in which corruption and integrity apply to everyday practices, ideas and ideologies, and avoids the stigmatizations and oversimplifications that often plague these fields of research.